Tibetan Buddhist Pilgrims and the covid-19 pandemic. Issue 9 (21st October 2021) - Benoit, Carol Teuton; Thomas, Patricia A.; Remley, Theodore P.
ABSTRACT: Vajrayana Buddhism, like all of the world's major religions, places high importance on the ancient practice of pilgrimage for spiritual development and maintenance of spiritual health. The negative mental health impacts of the COVID-19 pandemic reveal the need for exploring efficacious methods of religious coping, especially those closely associated with culture and tradition. This qualitative hermeneutical study was aimed at examining the impact of prior pilgrimage participation upon individuals experiencing the COVID-19 pandemic. Nine interviews were conducted with participants who had completed pilgrimage in the Vajrayana Buddhist tradition and were enduring the COVID-19 pandemic while embedded in western culture. Results elucidated the mechanisms and impacts of pilgrimage components upon multidimensional aspects of participants. Beneficial effects of pilgrimage on mental well-being were found including resilience building enacted through enhanced religious and spiritual coping and promotion of integration.